PENERAPAN GAYA EKSPOSITORI DALAM PENYUTRADARAN FILM DOKUMENTER “SABANGKA SAROPE” - Farid Khairil Ilman; Widhi - Nugroho (Texture:Art and Culture Journal, 2022)
The most popular voyage of the Barata Kahedupa community in the 1960s was the culture of Bhangka’s boat or sailing ship. The Bhangka was used as a warship for the Barata Kahedupa fleet and also used by the local community as a boat for trade. This film will lead the audience to understand the existing problems related to the bhangka;s boat culture which is currently approaching extinction. “Sabangka Sarope” film is packed with expository of documentary film style and a three-act structural narrative approach. Directing the expository documentary “Sabangka Sarope” by applying a three-act structure can help the audience to more easily understand the existing problems, especially in relation to the bhangka’s boat culture.